2009
DOI: 10.1177/1740774508101191
|View full text |Cite
|
Sign up to set email alerts
|

Confronting challenges in intervention research with ethnically diverse older adults: the USC Well Elderly II Trial

Abstract: Background-Community-dwelling older adults are at risk for declines in physical health, cognition, and psychosocial well-being. However, their enactment of active and health-promoting lifestyles can reduce such declines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 46 publications
(51 reference statements)
1
50
0
Order By: Relevance
“…Data from the Well Elderly 2 study (Clark et al, 2011;Jackson et al, 2009) are used to illustrate that the choice between M 2 and M 3 can make a practical difference. A general goal in the Well Elderly 2 study was to assess the efficacy of an intervention strategy aimed at improving the physical and emotional health of older adults.…”
Section: Illustrationsmentioning
confidence: 99%
“…Data from the Well Elderly 2 study (Clark et al, 2011;Jackson et al, 2009) are used to illustrate that the choice between M 2 and M 3 can make a practical difference. A general goal in the Well Elderly 2 study was to assess the efficacy of an intervention strategy aimed at improving the physical and emotional health of older adults.…”
Section: Illustrationsmentioning
confidence: 99%
“…Motivated by data stemming from the Well II study (Jackson et al 2009), this paper examines the impact of tied values on the probability of a Type I error when testing hypotheses via various robust regression estimators. Many of the dependent variables in the Well Elderly study were the sum of Likert scales.…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of cognitive preservation may not be obvious enough to serve as a reinforcer for continuous practice. Intervention studies on lifestyle modification for cardiovascular health and chronic diseases suggested that factors such as peer support, age, health status, self-efficacy, cognitive and mental conditions were facilitators and barriers to intervention (Jackson et al, 2009;Leijon et al, 2011;Griffo et al, 2012). It is also recognized that positive effects may cease after intervention stops, especially when supervised practice is no longer available (Lam et al, 2010).…”
Section: Barriers To Practicementioning
confidence: 99%